Purgatory in the Writings from Egypt and North Africa (lst-/Vth Century AD) - (:unkn) unknown (My University, 2012)
This thesis intends to reconsider the concept of purgatory as it was established and used by the historians of the late twentieth century; show that this redefined purgatory can be identified in some of the writings of Early Christianity, not always recognized by the mainstream Church; document that purgatory and place it in its historical, literary and religious context.The corpus includes the biblical sources considered to ground the representation of purgatory set against contemporary writings and texts from North Africa and Egypt, written between the second and fourth centuries AD, in Latin, Greek and Coptic. The selected writings allow us to appreciate the differences between the Christian doctrine of ecclesiastical authors and a more marginal spirituality, even though both share the same references.
Keywords: African Research